Analysis of Low Flow in Rantau Panjang, Sungai Johor - Koh, Lyn Jane (2015)
This study reviews the probability distribution functions suitable for low flow in Rantau Panjang, Sg. Johor. The daily discharge data was collected from the Department of Irrigation and Drainage. The proposed probability distribution functions are Gumbel distribution, Weibull distribution, Log-Pearson III distribution and Log-Normal distribution. The data obtained ranges from year 1975 to year 2014, 40 years of records. The Kolmogorov-Smirnov test and Chi-Squared test were used as the goodness of fit test to choose the best fit probability distribution.